Catalase: A critical node in the regulation of cell fate - Baker, Alison; Lin, Chi-Chuan; Lett, Casey; Karpinska, Barbara; Wright, Megan H.; Foyer, Christine H. (Free radical biology & medicine, 2023)
Catalase (CAT) is an extensively studied if somewhat enigmatic enzyme that is at the heart of eukaryotic antioxidant systems with a canonical role in peroxisomal function. The CAT family of proteins exert control over a wide range of plant growth and defence processes. CAT proteins are subject to many types of post-translational modification (PTM), which modify activity, ligand binding, stability, compartmentation and function. The CAT interactome involves many cytosolic and nuclear proteins that appear to be essential for protein functions. Hence, the CAT network of roles extends far beyond those associated with peroxisomal metabolism. Some pathogen effector proteins are able to redirect CAT to the nucleus and recent evidence indicates CAT can traffic to the nucleus in the absence of exogenous proteins. While the mechanisms that target CAT to the nucleus are not understood, CAT activity in the cytosol and nucleus is promoted by interactions with nucleoredoxin. Here we discuss recent findings that have been pivotal in generating a step change in our understanding of CAT functions in plant cells. [Display omitted] •Catalase is a central player in the cellular anti-oxidant network (67).•How catalase folds, assembles and imports into peroxisomes is not fully understood (84).•Catalase undergoes many posttranslational modifications (58).•Catalase has a large, dynamic interactome and is targeted by pathogen effectors.(83).•Catalase's cellular location is not fixed and may it exhibit moonlighting functions (85).